2019
DOI: 10.1093/ecco-jcc/jjz093
|View full text |Cite
|
Sign up to set email alerts
|

Endo-sponge Assisted Early Surgical Closure of Ileal Pouch-anal Anastomotic Leakage Preserves Long-term Function: A Cohort Study

Abstract: Background and Aims Endo-sponge [Braun Medical] assisted early surgical closure [ESC] is an effective treatment to control pelvic sepsis after ileal pouch-anal anastomosis [IPAA] leakage, and became standard treatment in our centre from 2010 onwards. The aim of this cohort study was to assess the long-term pouch function of ulcerative colitis [UC] patients treated with ESC or conventional management [CM] for anastomotic leakage after IPAA. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 26 publications
1
29
0
Order By: Relevance
“…Ileostomy-specific morbidity such as anastomotic leak, dehydration and renal failure are also well reported [29]. This study also confirms that active rescue of a failed anastomosis (endoscopic vacuum-assisted closure of the anastomotic defect) ensures IPAA healing and early stoma reversal [30,31]. For all these reasons, we do not create a diverting ileostomy unless technical difficulties are encountered during IPAA construction.…”
Section: Discussionsupporting
confidence: 71%
“…Ileostomy-specific morbidity such as anastomotic leak, dehydration and renal failure are also well reported [29]. This study also confirms that active rescue of a failed anastomosis (endoscopic vacuum-assisted closure of the anastomotic defect) ensures IPAA healing and early stoma reversal [30,31]. For all these reasons, we do not create a diverting ileostomy unless technical difficulties are encountered during IPAA construction.…”
Section: Discussionsupporting
confidence: 71%
“…Single-center studies using transanal vacuum-assisted closure therapy showed good short-term outcomes in terms of complete healing and ileostomy closure rate [150,151]. A recent report demonstrated that this treatment was associated with improved pouch function and a lower incidence of pouch failure compared to conventional management [152].…”
Section: Item 17 Anastomotic Leak After Ileal Pouch-anal Anastomosis (Ipaa) Should Be Treated Conservatively When Possible Anastomotic Dementioning
confidence: 99%
“… 7 , 9 A simple leak at the tip of the “J” has been treated with OTSC as demonstrated in a previous case series 7 and case reports. 12 , 13 Although endosponge or endoluminal vacuum-assisted therapy has been used for the treatment of acute anastomotic leaks after IPAA, 14 , 15 its role in the management of chronic leaks or fistulas has not been established.…”
Section: Discussionmentioning
confidence: 99%